In the people's court ; Children betrayed ; Reflections of Larry Alcala [videorecording] - Lazaro, Cheche (The Probe Team, 1995)
The trial of Hubert Webb is a much waited event. Pedophiles continue and the victims are street children. Interview with Larry Alcala in cartooning.